Artificial intelligence in genomic sequence, protein structure function prediction and DNA microarrays: a survey. (4th January 2010) - Vasilakos, Athanasios V.; Niu, Bing; Liu, Liang; Lu, Wencong
Bioinformatics is conceptualising biology in terms of molecules (in the sense of physical chemistry) and applying 'informatics techniques' (derived from disciplines such as applied mathematics, computer science and statistics) to understand and organise the information associated with these molecules on a large scale. In short, bioinformatics is a management information system for molecular biology and has many practical applications. Many artificial intelligence (AI) methods have been employed in the field of bioinformatics. In this paper, we will introduce the application of AI methods mainly in three fields: genomic sequence, protein structure and function prediction and DNA microarrays. AI methods surveyed in this paper cover artificial neural network, support vector machine (SVM), ensemble learning, hidden Markov model, and some other conventional method like rough set, decision tree, K-nearest neighbour.